2008
DOI: 10.3201/eid1401.071036
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus (H5N1) Replication in Feathers of Domestic Waterfowl

Abstract: We examined feathers of domestic ducks and geese inoculated with 2 different avian infl uenza virus (H5N1) genotypes. Together with virus isolation from the skin, the detection of viral antigens and ultrastructural observation of the virions in the feather epidermis raise the possibility of feathers as sources of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 14 publications
6
46
1
Order By: Relevance
“…10 A previous study in domestic ducks showed that H5N1 HPAI virus was able to be reisolated over a longer period from feathers than from oropharyngeal and cloacal swabs. 39 Similar results were found with H7N1 HPAI virus in chickens, where the viral titer in feather pulp was higher than in swabs. 4 For diagnostic purposes, feathers also have advantages over other sample types in that they are easy to collect, and their collection is minimally invasive.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…10 A previous study in domestic ducks showed that H5N1 HPAI virus was able to be reisolated over a longer period from feathers than from oropharyngeal and cloacal swabs. 39 Similar results were found with H7N1 HPAI virus in chickens, where the viral titer in feather pulp was higher than in swabs. 4 For diagnostic purposes, feathers also have advantages over other sample types in that they are easy to collect, and their collection is minimally invasive.…”
Section: Introductionsupporting
confidence: 75%
“…Virus was reisolated from feathers in an infection study using 2 H5N1 HPAI viruses in ducks and geese, 39 and virus was also detected in feathers of infected wild swan, 40 and of chickens, quail, turkey, pheasant, and chukar partridge. 14 H5N1 HPAI virus was still infective in feathers of infected ducks stored for >5 months at 4°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is likely to be because they used pre‐Qinghai Lake (2005) clade 1 isolates, and is evidence for the increased virulence for ducks of the clade 2.2 H5N1 variant that apparently emerged in the Qinghai Lake region of China in 2005 3 . Interestingly, virus was detected in wing feathers of both age groups, which has been demonstrated previously, 25 , 28 , 29 and is suggested as a possible sampling method for HPAI surveillance in wild bird populations. However, in older ducks in the present study, detection of virus was shown to be related to the level of calcification of the feather shaft and therefore the age of the bird sampled may affect the sensitivity of feather sampling as a method of surveillance.…”
Section: Discussionmentioning
confidence: 59%
“…and increased proportionally with viraemia levels. As feather pulp is highly vascularized, the elevated amounts of HPAIV may not be the only cause of an active replication in feather epidermal cells, as suggested previously (Yamamoto et al, 2008b); it may also be caused by the blood vascularizing these tissues. In infected carcasses, feather pulp was also one of the samples where the virus persisted for longer.…”
Section: Discussionmentioning
confidence: 60%